Clinical value of the quantitation of average daily platelet increase during the recovery period in childhood acute lymphoblastic leukaemia. (3rd October 2019) - Wang, Yuefang; Zhang, Ge; Ye, Lei; Dai, Qingkai; Peng, Luyun; Chen, Lan; Chen, Qi; Jiang, Yongmei; Gao, Ju
Abstract: The time to platelet recovery (TPR) is becoming a predicting factor during the treatment of childhood acute leukaemia. However, the initial pre-treatment platelet count (PPC) could interfere with TPR. Here, we integrated both TPR and PPC as the average daily platelet amount increase (Ap) to predict the prognosis in childhood B-ALL during the recovery period.148 patients were enrolled. The relationship between the Ap and MRD was evaluated, and Multivariate analysis was performed to evaluate whether Ap was independently associated with a better EFS. The PPC was inversely correlated with TPR ( r s = −0.519, P = 0.021). Patients in Ap >3.9 × 10 9 /L group had better EFS ( x 2 = 3.109, P = 0.028) than TPR ≤ 16d. Multivariate analysis indicated that Ap > 3.9 × 10 9 /L was independently associated with a longer EFS (RR = 3.468; 95%CI: 1.037–11.597, P = 0.043). However, when introducing both MRD and Ap > 3.9 × 10 9 /L as candidate variables, the Ap > 3.9 × 10 9 /L lost its independent effect ( P = 0.081). The strong association between MRD on treatment day 33 and Ap > 3.9 × 10 9 /L ( x 2 = 148.00, P = 0.000) was responsible for this phenomenon. Ap could be a valuable prognostic indicator in childhood B-ALL.